Designs of infrared nonpolarizing beam splitters with a Ag layer in a glass cube - Shi, Jin Hui; Wang, Zheng Ping (Applied optics (2004), 2008)
A novel design of a nonpolarizing beam splitter with a Ag layer in a cube was proposed and optimized, based on the needle optimization. The digital simulations of the reflectance and reflection-induced retardance were presented. The simulation results showed that both the amplitude and the phase characteristics of the nonpolarizing beam splitter could realize the design targets. The difference between the simulated and the target reflectance of 50% is less than 0.4% and the simulated and the reflection-induced retardance is less than 0.62 degrees in the 1260 -1360 nm range for both p and s components.